Pengujian Skala Laboratorium Performa Rotor Turbin Angin Ganda Kontra-Rotasi Melalui Variasi Rasio Geometri - PAE, KOSTAN; Koehuan, Verdy A.; Gurnawati, Gurnawati (Universitas Nusa Cendana, 2024)
The aim of this research is to determine the performance of a double rotor counter-rotation wind turbine on the geometric configuration of the CRWT rotor ratio. Tests were carried out on a laboratory scale with a turbine rotor blade model using the S826 airfoil series issued by NREL (National Renewable Energy Laboratory), where the rotor diameter at field scale (full scale) was 0.944 m. The blade is made through a 3D printing process using PLA (polylactic acid) material with an S826 airfoil profile. Laboratory scale testing uses a wind tunnel with test section dimensions of 0.6 m long, 0.3 m wide and 0.3 m high and the wind speed is considered uniform, varying from 3 m/s to 5 m/s. The performance of CRWT with rotor geometry ratio D1/D2 < 1 is better than CRWT with rotor geometry ratio D1/D2 > 1 at rotor distance Z/D1= 0.4. Varying the turbine geometry ratio with a smaller front rotor diameter, the power coefficient of the front rotor turbine is higher than the turbine with a larger front rotor diameter.